WONDERFUL INDONESIA: CITRA POSITIF PARIWISATA INDONESIA MELALUI ASEAN TOURISM FORUM 2018 – 2019 - Achmad Habib Dwi Prakoso; Raditya Abdurrahman Nugraha; Megahnanda Alidyan Kresnawati (Universitas Halu Oleo, 2022)
This study aims to find out the positive image of Indonesian tourism through the Asean Tourism forum in 2018 - 2019. This research will use descriptive qualitative research methods. This method is intended to explore and clarify a phenomenon or social reality by describing a number of variables relating to the problem and unit under study. The study results show that in 2018, Indonesia's tourism growth showed a good increase. According to a report by The World Travel and Tourism Council (WTTC), Indonesia is ranked 9th in the world, number 3 in Asia, and number 1 in ASEAN, which means that it is ranked at the top of other Southeast Asian countries. Indonesia participated in the ASEAN Tourism Forum, a forum between ASEAN countries experienced by various tourism industries. Indonesia, as the best tourism in ASEAN, wants to build a positive image through the ASEAN Tourism forum 2018-2019. The embodiment of this positive image will use Anholt's three image formation processes: strategy, substance, and symbolic action. Through this explanation, this paper will discuss how the idea of Indonesian tourism is formed through the role of Wonderful Indonesia and the process through the ASEAN Tourism Forum as a whole.